2002
DOI: 10.1016/s1534-5807(02)00188-0
|View full text |Cite
|
Sign up to set email alerts
|

The IGF-1/Akt Pathway Is Neuroprotective in Huntington's Disease and Involves Huntingtin Phosphorylation by Akt

Abstract: In the search for neuroprotective factors in Huntington's disease, we found that insulin growth factor 1 via activation of the serine/threonine kinase Akt/PKB is able to inhibit neuronal death specifically induced by mutant huntingtin containing an expanded polyglutamine stretch. The IGF-1/Akt pathway has a dual effect on huntingtin-induced toxicity, since activation of this pathway also results in a decrease in the formation of intranuclear inclusions of mutant huntingtin. We demonstrate that huntingtin is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
369
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(404 citation statements)
references
References 33 publications
28
369
1
6
Order By: Relevance
“…Reduced Akt was previously reported in HD patients, appearing as a shorter inactive caspase-3-cleaved form [27,75]. Corroborating our study, p-(Ser473)Akt/Akt levels were significant decreased in STHdh Q111/Q111 cells [76], in HEK293 cells expressing mHtt with 68 CAG repeats [77] and in HD patient's lymphoblasts and lymphocytes [75].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reduced Akt was previously reported in HD patients, appearing as a shorter inactive caspase-3-cleaved form [27,75]. Corroborating our study, p-(Ser473)Akt/Akt levels were significant decreased in STHdh Q111/Q111 cells [76], in HEK293 cells expressing mHtt with 68 CAG repeats [77] and in HD patient's lymphoblasts and lymphocytes [75].…”
Section: Discussionsupporting
confidence: 89%
“…Corroborating our study, p-(Ser473)Akt/Akt levels were significant decreased in STHdh Q111/Q111 cells [76], in HEK293 cells expressing mHtt with 68 CAG repeats [77] and in HD patient's lymphoblasts and lymphocytes [75]. Akt activation is an early pro-survival striatal response in knock-in Hdh Q111 mice and STHdh Q111/Q111 cells [28]; importantly, activation of IGF-1/Akt pathway caused Htt phosphorylation at Ser421, decreasing mHtt nuclear inclusions and mHtt toxicity [27] and regulated anterograde and retrograde transport defects in HD cortical neurons [78]. Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor-I (IGF-I) signaling is involved in muscle atrophy and degeneration, 28,29 and in the pathogenesis of various neurodegenerative disorders, including s-IBM. [30][31][32][33] Therefore, we evaluated the expression of two major antiapoptotic signaling molecules, activated downstream to IGF receptor: MAPK (extracellularly regulated kinase 1/2 (ERK1/2)), activated via Ras-Raf and Akt/PKB (protein kinase B), activated via phosphatidylinositol 3-kinase (PI3K). 34 The ERK1/2 cascade promotes cellular proliferation, survival and growth, through processes of DNA synthesis and cell-cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…mHtt is phosphorylated at S421 by Akt, and its dephosphorylation depends on the phosphatases PP1/ PP2A 107,108 , whereas APP is phosphorylated by Cdk5 and Gsk3β in neurons 104 (Suppl Table S3). Gsk3β is also the major kinase phosphorylating Tau in AD, which leads to the formation of insoluble Tau aggregates (Tau tangles) and subsequent disruption of the microtubule system 67 .…”
Section: Kinases and Phosphatasesmentioning
confidence: 99%